Light-dependent spatiotemporal control of plant cell development and organelle movement in fern gametophytes. (20th December 2018) - Wada, Masamitsu
Abstract: The haploid gametophyte generation of ferns is an excellent experimental material for cell biology studies because of its simple structure and high sensitivity to light. Each step of the developmental process, such as cell growth, cell cycle and the direction of cell division, is controlled, step by step, by light, unlike what happens in complex seed plant tissues. To perform analyses at the cell or organelle level, we have developed special tools, instruments and techniques, such as a cuvette suitable for repeated centrifugation in particular directions, microbeam irradiators for partial cell irradiation and single-cell ligation technique to create enucleated cells. Some of our main discoveries are as follows: (1) changes in the intracellular position of the nucleus in long protonemal cells by centrifugation revealed that the nuclear position or a factor(s) that is/are co-centrifuged with the nucleus is important for the decision regarding the place of the formation of preprophase bands and the timing of their disappearance, which determines the position where the new cell wall attaches to the mother cell wall; (2) even within a single cell, various phenomena could be induced by blue or red light, with the localization of the blue or red light receptors being different depending on the phenomenon; (3) de novo mRNA synthesis is not involved in the signal transduction pathways underlying light-induced chloroplast movements. In this review article, various microscopic techniques, in addition to the results of physiology studies in fern gametophytes, are described.